Targeting protein tyrosine phosphatases for CDK6-induced immunotherapy resistance - Gao, Xueliang; Wu, Yongxia; Chick, Joel M.; Abbott, Andrea; Jiang, Baishan; Wang, David J.; Comte-Walters, Susana; Johnson, Roger H.; Oberholtzer, Nathaniel; Nishimura, Michael I.; Gygi, Steven P.; Mehta, Anand; et al. (Cell reports (Cambridge), 2023)
Elucidating the mechanisms of resistance to immunotherapy and developing strategies to improve its efficacy are challenging goals. Bioinformatics analysis demonstrates that high CDK6 expression in melanoma is associated with poor progression-free survival of patients receiving single-agent immunotherapy. Depletion of CDK6 or cyclin D3 (but not of CDK4, cyclin D1, or D2) in cells of the tumor microenvironment inhibits tumor growth. CDK6 depletion reshapes the tumor immune microenvironment, and the host anti-tumor effect depends on cyclin D3/CDK6-expressing CD8+ and CD4+ T cells. This occurs by CDK6 phosphorylating and increasing the activities of PTP1B and T cell protein tyrosine phosphatase (TCPTP), which, in turn, decreases tyrosine phosphorylation of CD3ζ, reducing the signal transduction for T cell activation. Administration of a PTP1B and TCPTP inhibitor prove more efficacious than using a CDK6 degrader in enhancing T cell-mediated immunotherapy. Targeting protein tyrosine phosphatases (PTPs) might be an effective strategy for cancer patients who resist immunotherapy treatment. [Display omitted] •CDK6 expression in the tumor microenvironment shapes a pro-tumor microenvironment•CDK6 activates PTP1B and TCPTP to de-phosphorylate CD3ζ and decrease T cell activity•Targeting PTPs lessens resistance to immunotherapy•Targeting PTPs may augment adoptive T cell therapy for cancer patients Using genetic and pharmaceutical approaches, Gao et al. investigate the distinct roles of CDK4 and CDK6 in the TME to regulate tumor growth and evaluate the therapeutic potential of the CDK6-PTP-CD3ζ axis in adoptive T cell therapy.